2015
DOI: 10.1111/fcsr.12130
|View full text |Cite
|
Sign up to set email alerts
|

Family and Consumer Sciences Graduate Research Productivity in 2014

Abstract: Requests to collect the titles of theses and dissertations completed in 2014 were sent to representatives of 140 universities and colleges with family and consumer science programs in April 2015. Representatives from 44 universities responded, reporting a total of 533 theses and dissertations. Of those titles, 356 were for theses and 177 were for dissertations. The greatest number of titles reported for theses was in Nutrition and Dietetics and for dissertations was in Marriage and Family Therapy. An additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 1 publication
2
16
0
Order By: Relevance
“…For master's theses, the category with the highest number of titles reported was nutrition and dietetics (33.2%), followed by human development (12.6%) and child development (8.7%). The large numbers in three categories have been consistent in the past several years, including those reported in 2015 for master's theses (Kabaci, ). For doctoral dissertations, the category with the highest number of titles reported was nutrition and dietetics (15.6%), followed by human development (14.9%) and family relations (13.8%).…”
Section: Subject Matter Categoriessupporting
confidence: 76%
See 2 more Smart Citations
“…For master's theses, the category with the highest number of titles reported was nutrition and dietetics (33.2%), followed by human development (12.6%) and child development (8.7%). The large numbers in three categories have been consistent in the past several years, including those reported in 2015 for master's theses (Kabaci, ). For doctoral dissertations, the category with the highest number of titles reported was nutrition and dietetics (15.6%), followed by human development (14.9%) and family relations (13.8%).…”
Section: Subject Matter Categoriessupporting
confidence: 76%
“…Thirty‐five institutions submitted information for theses and dissertations completed in 2015. This number was a decrease from the 39 institutions that participated in the previous year (Kabaci, ) (see Table ). The decrease may be due to fewer graduate students completing dissertations or theses in 2015 than in previous years.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Of that total number, 259 (57.2%) were theses, and 194 (42.8%) were dissertations. As identified in previous articles (e.g., Kabaci, 2015;Pucciarelli & Faith, 2012) nonthesis options for master's degrees continue to have a large share of reported degrees in family and consumer sciences. In 2016, 24 (68.6%) of the participating programs reported that 655 students completed nonthesis master's degree options.…”
Section: Resultsmentioning
confidence: 83%
“…Turing to doctoral dissertations, the largest category with 14.95% of titles submitted was in institution, hotel, and restaurant management. This is a change as in recent years the top category has been nutrition and dietetics (2015), marriage and family therapy (2014), and family relations (2013) (Kabaci, ; Kabaci ; Kabaci ). The second and third categories for doctoral dissertations were close in numbers to the first, with nutrition and dietetics in second place (14.43%) and human development in third place (12.89%).…”
Section: Subject Matter Categoriesmentioning
confidence: 99%